2018
DOI: 10.1037/qup0000078
|View full text |Cite
|
Sign up to set email alerts
|

Social citizenship and immigration: Employment, welfare, and effortfulness in online discourse concerning migration to the United Kingdom.

Abstract: Research at York St John (RaY) is an institutional repository. It supports the principles of open access by making the research outputs of the University available in digital form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Gibson, Crossland, and Hamilton (2017) demonstrated how arguments about "social citizenship" were used to argue against allowing EU migration into the UK, here with categories such as "East European" and "immigrants" being presented as particularly likely to claim welfare benefits and therefore to be a financial burden on the UK. Gibson, Crossland, and Hamilton (2017) demonstrated how arguments about "social citizenship" were used to argue against allowing EU migration into the UK, here with categories such as "East European" and "immigrants" being presented as particularly likely to claim welfare benefits and therefore to be a financial burden on the UK.…”
Section: Discursive Research and Anti-immigration Argumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gibson, Crossland, and Hamilton (2017) demonstrated how arguments about "social citizenship" were used to argue against allowing EU migration into the UK, here with categories such as "East European" and "immigrants" being presented as particularly likely to claim welfare benefits and therefore to be a financial burden on the UK. Gibson, Crossland, and Hamilton (2017) demonstrated how arguments about "social citizenship" were used to argue against allowing EU migration into the UK, here with categories such as "East European" and "immigrants" being presented as particularly likely to claim welfare benefits and therefore to be a financial burden on the UK.…”
Section: Discursive Research and Anti-immigration Argumentsmentioning
confidence: 99%
“…Gibson and colleagues have focused specifically on talk about EU migration into the UK, and the ways in which this is designed to justify the exclusion of migrants. Gibson, Crossland, and Hamilton (2017) demonstrated how arguments about "social citizenship" were used to argue against allowing EU migration into the UK, here with categories such as "East European" and "immigrants" being presented as particularly likely to claim welfare benefits and therefore to be a financial burden on the UK. Gibson (2015) showed how Polish migrants were presented by young English participants as problematic in terms of the economy, their different culture and because they could be threatening and intimidating.…”
Section: Discursive Research and Anti-immigration Argumentsmentioning
confidence: 99%
“…And the rhetorical nature of discourse and debate implies a focus on how different common sense notions are used to work up particular identities and versions of reality in opposition to potential alternative ones (Billig, ). A discursive and rhetorical approach has successfully been used for analysing political debates in relation, for example, to fact‐based (counter)claims (Demasi, ), social citizenship and immigration (Gibson, Crossland, & Hamilton, ), anti‐establishment rhetoric (Rooyackers & Verkuyten, ), and the discursive construction of ‘otherness’ in political blogs (Sakki & Pettersson, ). The approach allows us to examine how controversy and contestation unfold as situated practices and the implications that this has for political identities and marginality.…”
Section: Materials and Analytical Approachmentioning
confidence: 99%
“…In the past 20 years, social psychology has increasingly engaged with citizenship as a topic, contributing useful insights into how people both understand and perform citizenship in various contexts. However, such approaches have largely concentrated on political and civil citizenship, overlooking the social dimension (Gibson, Crossland, & Hamilton, ). This paper makes the case for social citizenship as a useful and important topic for social psychological research and outlines work done in this area to date from outside the discipline.…”
Section: Introductionmentioning
confidence: 99%
“…As our arguments are shaped by the material conditions of our lives and personal histories, as well as wider societal influences, this approach allows for a rich exploration that can also incorporate other complex factors such as class, gender, culture, ethnicity, and even health status (McAvoy, ). Of the small amount of discursive social psychological research that explicitly deals with social citizenship as a topic, Gibson et al () focus on the intersection of social citizenship and immigration. In their analysis of online comments about immigration, they found that issues around welfare were often invoked and a repertoire of “effortfulness” was frequently used to negotiate debates about who was or wasn't entitled to the status of full, competent citizen.…”
Section: Introductionmentioning
confidence: 99%